A Study on small and medium enterprises awareness and practices of pre-development implementation - Abu, Noor Hidayah; Md Deros, Baba; Abd Wahab, Dzuraidah; Mansor, Mohd Fitri (2013)
Pre-development process is an important driver for organizations to improve their performance and sustain competitiveness.Large-scale organizations have received full attention from many researchers with respect to efficient pre-development implementation and practices. However, small and medium enterprises (SMEs) did not received adequate attention from the research community for their pre-development practices.This study was performed with the main objective to identify different practicing between Malaysian food and beverage manufacturing SME and large organization in implementation of pre-development process.To do this a survey questionnaire was developed and pilot tested to ensure its validity and reliability. Later, the survey questionnaire was sent to 687 Malaysian food and beverage manufacturing SMEs to identify their practicing on pre-development process implementation. Descriptive analysis was carried out to determine respondent profile and rank of five critical success factors (CSFs) based on it s contribution.Tests to investigate any differences between SMEs and large organization in pre-development implementation practices were conducted using MANOVA and ANOVA analysis.The results of the study indicated that there is significant difference between SMEs and large organization in practicing pre- development process implementation. Both of the companies agreed that idea generation phase, commitment top management and project team members are important factor during pre-development process implementation.However they have different perspectives on the level of importance for factors: concept development phase, project evaluation phase, clear product strategy, external organization involvement and training during the implementation process.The results presented a clarified view of pre-development implementation practice based on the Malaysian food and beverage manufacturing SME perspective.